Successful treatment of pityriasis lichenoides chronica with narrow-band ultraviolet B therapy in a patient with Keratitis-Ichthyosis-Deafness syndrome: a case report - (:unkn) unknown (My University, 2016)
Keratitis-ichthyosis-deafness (KID) syndrome is a rare genodermatosis causing ichthyosis-like skin lesions, keratitis, and deafness. Herein, we report a patient with this rare syndrome in association with pityriasis lichenoides chronica, which was succesfully treated with narrow-band ultraviolet B phototherapy despite our concerns regarding the increased risk of squamous cell carcinoma, hyperpyrexia, and keratitis.
Keywords: Humans; Male; Child; Keratitis; Pityriasis Lichenoides; Ultraviolet Therapy